Sustainable environmental manufacturing practices and firm performances: moderating role of environmental regulation and perceived benefits - Olusegun, Adebambo Hameed (2015)
More attention has been shifted to the environmental impacts of manufacturing companies on firm performance as sustainable environmental manufacturing practice has become an issue of concern to most researchers and practitioners. Theoretical evidence from previous studies showed that a considerable amount of attention has been given to environmental issues in academic studies in the past years and the link between environmental practices and performance of firms has been widely discussed, which results into different views. Thus, the relationship between sustainable environmental practices and firm performance remains inconclusive. This study investigates the impact of sustainable environmental manufacturing practices (SEMP) on firm performance through the moderating effects of perceived benefits (PB) and environmental regulation (ER). In addition, the relationships between the antecedent factors and SEMP were investigated. Data was collected from manufacturing companies in Malaysia using a cross sectional study design and stratified random sampling method. 103 usable questionnaires were collected by using a mail survey method and analysed with SmartPLS-SEM. The result indicated that five out of the 12 hypothesized relationships (both the direct and moderating hypotheses) were supported. Specifically, the study found that top management commitment and stakeholder pressure positively influence sustainable environmental manufacturing practices and that sustainable environmental manufacturing practice has a direct positive influence on environmental performance. The study also established that perceived benefits moderates the relationship between sustainable environmental manufacturing practice and operational performance, while the relationship between sustainable environmental manufacturing practice and environmental performance is moderated by environmental regulation. In addition, it was found that sustainable environmental manufacturing practice is still regarded as ethical behaviour and yet to be considered as a strategic factor of firms in Malaysia. Hence, important implication f this study to the environmental regulatory policy makers, academics and manufacturing practitioners in Malaysia is to create more awareness on the perception of SEMP as a strategic factor towards achieving better firm performance. It also reveals the need for environmental policy makers and the concerned authorities to revisit the environmental regulations on manufacturing practices to provide supportive environmental policies that will enhance a better firm performance in the Malaysian manufacturing industry.